Optimal Design of Transport and Reaction Pattern in Premixed Methane-air Micro-combustor - Cao, Xuepu; Jia, Shengkun; Luo, Yiqing; Yuan, Xigang; Yu, Kuo-Tsong (Computer Aided Chemical Engineering, 2018)
The importance of developing micro-combustor with high efficient is apparent, due to the demand for miniature power source with high energy density. A two-dimension model of micro-combustor for a premixed methane/air mixtures combustion process, under the condition of stable burning, was constructed. The availability and the entropy generation of the combustion were analyzed. The minimum of entropy generation was set as the objective function, subject to a constraint of constant viscous dissipation. Through variation calculation, an optimal velocity field and associate body force field were obtained. Such a solution provided a thermodynamic limit to the enhancement of the combustion process. Inspired by the flow field obtained by the optimization, an improved internal structure of the micro-combustor that gave a higher efficiency was suggested and analyzed. The results obtained can provide a guideline for the design of micro-combustor with high burning efficiency.